FBE Ubaya students' use of ULS in the perspective of the UTAUT model - Calista Kurniawan; Fitri Widjaja; Veny Megawati; Muhammad Gunawan Wibisono (Faculty of Business and Economics, University of Surabaya, 2025)
This study aims to analyze the factors influencing the intention and behavior of Business and Economics Faculty (FBE) students at Surabaya University in using the Ubaya Learning Space (ULS) based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The UTAUT model, developed by Venkatesh et al., comprises four main variables: performance expectancy, effort expectancy, social influence, and facilitating conditions, as well as two dependent variables, behavioral intention and use behavior. Data was collected through questionnaires distributed to active 2021-2023 FBE UBAYA students who use ULS. Structural Equation Modeling (SEM) analysis using AMOS V23 was employed to analyze the data. The findings indicate that performance expectancy, effort expectancy, social influence, and facilitating conditions have a positive and significant impact on behavioral intention. Moreover, behavioral intention has a significant positive impact on use behavior. These findings are expected to provide insights for UBAYA in developing and improving the effectiveness of ULS as an adaptive online learning platform that meets the needs of students.